Reaction of immunity indicators to change in nutrition - Burikov A. V. (Interactive science, 2018)
the article presents the results of a complex study of the introduction of vitamin and microelement complexes with the pharmacological adaptogen on the immunological resistance of the young people. There is a more pronounced increase in the functional capacity of the organism under the influence of vitamin and microelement additives to food, especially in combination with the pharmacologically adaptogen, due to the positive effect of these complexes on the intensity of the exchange of trace elements, mainly iron, on hematopoiesis and immunological reactivity of the organism.
Keywords: коррекция; витамины; микроэлементы; рацион питания; correction; vitamins; иммунологическая реактивность; food ration; immunological reactivity; microelements